Peel testing of a packaging material laminate studied by in-situ X-ray tomography and cohesive zone modeling. (December 2019) - Pettersson, Simon; Engqvist, Jonas; Hall, Stephen; Toft, Nils; Hallberg, Håkan
Abstract: Peel testing is used to study adhesive fracture in packaging material laminates. The focus is on improved understanding of the mechanisms that provide a laminate's adhesive properties, as measured by standard macroscopic tests. Using a specially-designed peel test load rig, peel tests are performed in-situ in a laboratory X-ray tomograph. The peel test results are analyzed using a combination of theoretical models for the adhesive fracture and 3D finite element simulations based on a cohesive zone model approach. Complementary experiments are performed to characterize the properties of the peel arm material. Relaxation of the material is found to occur during image acquisition in the in-situ tests. Despite this, it is possible to obtain 3D reconstructions with good quality during peeling. Peel test properties like the peel arm's root rotation angle and peel arm thinning are quantified. In the present 90° peel tests, it is found that the delamination progresses in an inhomogeneous manner, with the edges delaminating before the center. A number of issues and mechanisms during the peel test are identified. As an example, the peel arm itself can sometimes split, leaving residues of adhesive on the substrate surface. Such phenomena indicate the ambiguities involved in assessing adhesion properties from standard macroscopic force-displacement measurements, without accounting for the mechanisms involved on finer length scales.